Pemuridan Digital dan Pembentukan Spiritualitas Jemaat di Era Pascapandemi: Kajian Teologi Praktika Kristen - Esa Tedja Mahananie (Sekolah Tinggi Teologi Bethel Ambon, 2025)
This article discusses digital discipleship as a praxis of Christian practical theology in shaping congregational spirituality in the post-pandemic era. The transformation of church ministry during the COVID-19 pandemic shows that digital space no longer functions merely as a temporary tool, but has become part of the ecology of ecclesial ministry. The main issue examined is how the church can develop digital discipleship that remains biblical, relational, transformative, and pastorally responsible. This article uses a practical theology review method with a literature study approach. The analysis is structured through a dialogue between the reality of digital ministry, practical theology theory, and recent research findings on discipleship among the digital generation. The findings show that digital discipleship is effective when the church does not understand it as a substitute for the fellowship of the body of Christ, but as an extension of the space for faith formation. Digital discipleship needs to integrate doctrinal teaching, spiritual accompaniment, small communities, spiritual practices, digital literacy, and pastoral accountability. This article offers an integrative digital discipleship model that connects online and offline spaces to shape congregational spirituality that is mature, missional, and resilient.